Bank Ownership and Lending Behavior - Alejandro Micco; Ugo Panizza (Inter-American Development Bank, Research Department, 2004)
This paper examines whether bank ownership (public versus private, domestic versus foreign) is correlated with bank lending behavior over the business cycle. The paper finds that state-owned banks may play a useful credit-smoothing role because their lending is less responsive to macroeconomic shocks than the lending of private banks. The paper investigates whether this differential behavior is due to an explicit objective of stabilizing credit or to the presence of lazy public bank managers; evidence is found in support of the former hypothesis. In the case of foreign-owned banks, the paper finds that the results are less clear-cut and argues that this finding is in line with existing theoretical models.
Keywords: G21; H11; E44; 330; State-owned banks; Foreign-owned banks; Credit cycle; Bank; Eigentümer; Internationale Bank; Kreditgeschäft; Welt